On the Use of Simulated Annealing to Automatically Assign Decorrelated Components in Second Order Blind Source Separation - Böhm, M. (2006)
In this paper, an automatic assignment tool, called BSS-AutoAssign, for artifact-related decorrelated componentes within a second-order blind source separation (BSS) is presented. The latter is based on the recently proposed algorithm dAMUSE, which provides an elegant solution to both the BSS and the denoising problem simultaneously. BSS-AutoAssign uses a local principal component analysis (PCA)to approximate the artifact signal and defines a suitable cost function which is optimized using simulated annealing. The algorithms dAMUSE plus BSS-AutoAssign are illustrated by applying them to the separation of water artifacts from two-dimensional nuclear overhauser enhancement (2-D NOESY) spectroscopy signals of proteins dissolved in water.